2014
DOI: 10.4000/asp.4564
|View full text |Cite
|
Sign up to set email alerts
|

L’anglais de spécialité en LEA à la croisée des domaines : étude de l’acquisition du lexique spécialisé

Abstract: Intersections-l'anglais de spécialité, creuset multidomaine L'anglais de spécialité en LEA à la croisée des domaines : étude de l'acquisition du lexique spécialisé

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Previous studies on students' and teachers' representations (McAllister & Narcy-Combes, 2015;McAllister et al, 2012;Narcy-Combes & McAllister, 2011; on the development of accuracy, fluency, and complexity of written production between the beginning and the end of the programme (McAllister, 2013;McAllister & Belan, 2014) and on the students' use of the virtual resource center (McAllister, 2013;Starkey-Perret, McAllister, Belan, & Ngo, 2015) showed that although the programme is generally appreciated for the opportunities it generates for small-group interaction (McAllister et al, 2012;Starkey-Perret et al, 2012), students and teachers tend to prefer a PPP approach, claiming that TBLT does not leave sufficient room for FonF (Belan & Buck, 2012;McAllister, 2013). Questionnaire studies carried out with the students showed that the way 'grammar' is dealt with is the least satisfactory element of the programme and that there simply is not enough FonF (Belan & Buck, 2012).…”
Section: Student and Teacher Representationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies on students' and teachers' representations (McAllister & Narcy-Combes, 2015;McAllister et al, 2012;Narcy-Combes & McAllister, 2011; on the development of accuracy, fluency, and complexity of written production between the beginning and the end of the programme (McAllister, 2013;McAllister & Belan, 2014) and on the students' use of the virtual resource center (McAllister, 2013;Starkey-Perret, McAllister, Belan, & Ngo, 2015) showed that although the programme is generally appreciated for the opportunities it generates for small-group interaction (McAllister et al, 2012;Starkey-Perret et al, 2012), students and teachers tend to prefer a PPP approach, claiming that TBLT does not leave sufficient room for FonF (Belan & Buck, 2012;McAllister, 2013). Questionnaire studies carried out with the students showed that the way 'grammar' is dealt with is the least satisfactory element of the programme and that there simply is not enough FonF (Belan & Buck, 2012).…”
Section: Student and Teacher Representationsmentioning
confidence: 98%
“…The TBLT framework is now commonly used in ESP courses as it allows to meet learners' specific needs (Dudley-Evans & St John, 1998) by introducing real-world tasks whose completion implies managing both subject-specific content and language to produce meaning (Llinares & Dalton-Puffer, 2015;. This approach has been shown to help enhance language development in terms of fluency (McAllister & Belan, 2014). A study of the development of accuracy is also particularly relevant in ESP as learners' needs include acquiring professional competence in English, which is partly judged on language accuracy.…”
Section: Introductionmentioning
confidence: 99%